La oferta de turismo rural en el Noroeste de la región de Murcia - Espejo Marín, Cayetano (Geographicalia, 2017)
Along the last years, new experiences of tourist promotion with a rural character have begun to be developed at the area north-west of Murcia. In this article we analyse the different tourist products which are offered by this area, as well as the paper realized by the administration for its development, the tourist resources and the actions foreseen for the future.